Contributions of the macroion and counterions to the internal energy of fullerene electrolyte solutions - Škerjanc, Jože (Acta chimica slovenica, 2001)
From the solution of the Poisson-Boltzmann equation for the spherical celll model of a fullerene electrolyte solution, the contributions of the fullerene macroion and counterions to the electrostatic energy of the solution are calculated. Computations are made for solutions containing mixtures of counterions differing in size and charge. The results are presented as functions of the macroion concentration and mole fractions of the counterions.
Keywords: elektroliti; elektrostatska energija; fulereni; makroioni; modeli; protiioni; raztopine